A Pilot Study of Cancer-Induced Bone Pain Using Validated Owner Questionnaires, Serum N-Telopeptide Concentration, Kinetic Analysis, and PET/CT - Flesner, Brian K.; Torres, Bryan T.; Hutcheson, Kyle D.; Rindt, Hansjörg; Zalcman, Amy R.; Maitz, Charles A. (Frontiers in Veterinary Science, 2021)
Cancer-induced bone pain, despite its frequency and severity, is a poorly understood phenomenon in people and animals. Despite excitement regarding translational osteosarcoma studies, there is a lack of attention toward examining cancer pain in dogs. In this pilot study, we used a multimodal pain assessment methodology to evaluate pain relief after therapeutic intervention in dogs with primary bone cancer. We hypothesized that intervention would cause objective evidence of pain relief. Evaluations of 8 dogs with primary bone cancer included 18F-FDG PET/CT scans, kinetic analysis, validated owner questionnaires (Canine Brief Pain Inventory, canine BPI), and serum N-telopeptide (NTx) concentration. Dogs were routinely staged and had 18F-FDG PET/CT scans prior to treatment with day 0, 7, 14, and 28 canine BPI, serum NTx, orthopedic exam, and kinetic analysis. Dogs treated with zoledronate and radiation underwent day 28 18F-FDG PET scans. All clinical trial work was approved by the University of Missouri IACUC. Four dogs underwent amputation (AMP) for their appendicular bone tumors; four received neoadjuvant zoledronate and hypofractionated radiation therapy (ZOL+RT). Canine BPI revealed significant improvements in pain severity and pain interference scores compared to baseline for all dogs. Positive changes in peak vertical force (+16.7%) and vertical impulse (+29.1%) were noted at day 28 in ZOL+RT dogs. Dogs receiving ZOL+RT had a significant (at least 30%) reduction in serum NTx from baseline compared to amputated dogs (p = 0.029). SUVmax (p = 0.11) and intensity (p = 0.013) values from PET scans decreased while tumor uniformity (p = 0.017) significantly increased in ZOL+RT-treated tumors; gross tumor volume did not change (p = 0.78). Owner questionnaires, kinetic analysis, and 18F-FDG PET/CT scans showed improved pain relief in dogs receiving ZOL+RT. Serum NTx levels likely do not directly measure pain, but rather the degree of systemic osteoclastic activity. Larger, prospective studies are warranted to identify the ideal objective indicator of pain relief; however, use of multiple assessors is presumably best. With improved assessment of pain severity and relief in dogs with cancer, we can better evaluate the efficacy of our interventions. This could directly benefit people with cancer pain, potentially decreasing the amount of subtherapeutic novel drugs entering human clinical trials.